C++ Rush: an educational gaming experience / Arifah Fasha Rosmani and Muhammad Salman Hakim Shaiful Nizam - Rosmani, Arifah Fasha; Shaiful Nizam, Muhammad Salman Hakim (Universiti Teknologi MARA, Perlis, 2024)
Programming language is a subject that is quite difficult to understand at first glance, especially for beginners. Most beginners struggle to comprehend programming concepts because of their low maturity level, lack of programming experience, and difficulty understanding and learning the logic and scripting language. C++ is one of the basic, convenient programming languages that help programmers comprehend the principles of all programming languages. If the principles of C++ have been grasped, someone with a thorough knowledge of the language could easily transit to other programming languages. Therefore, this study proposes the combination of an educational game with C++ to provide early exposure to novice programmers and assist those who are struggling to learn the programming language. Furthermore, it attempts to create and develop an interactive, instructional programming game. Another purpose of this study is to test the usefulness of the generated programming game using a questionnaire. The study utilized the Agile Model because iterative development is one of its components. The agile technique consists of six (6) phases: requirements, design, development, testing, deployment, and review. This study did usability testing with 30 individuals. Most of them agreed that gamification might change a tough and complex topic into one that would be incredibly engaging. In addition, it has ultimately allowed users to properly learn C++. Future work may employ a broader range of programming languages.